2016
DOI: 10.1177/026248931603500302
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of High Temperature Polyphenylsulfone Nanofoams Using High Pressure Liquid Carbon Dioxide

Abstract: In this paper, we describe fabrication of micro- and nano-structured foams in high temperature polyphenylsulfone (PPSU) with a Tg of 219°C using a solid-state carbon dioxide (CO2) foaming process. We have fabricated microcellular foams with cell size in 1–10 μm range, and for the first time, nanocellular foams with cell size in 20–40 nm range. We discovered a critical CO2 concentration window 10.5%–11.8%, where a rapid 2–3 orders of increase in cell nucleation density is observed and cell size drops to below 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…The use of acetone induced crazing within the polymer thus resulting in a porous structure on the microcell walls. Without the use of organic solvents, Sorrentino et al [ 20 ] and Guo et al [ 21 , 22 , 23 ] developed foams with a similar structure. They investigated the foaming of high performance polymers including PESU and found that PESU exhibited nanocellular foams whereas the other investigated polymers exhibited pores with a diameter only in the micrometer range.…”
Section: Introductionmentioning
confidence: 99%
“…The use of acetone induced crazing within the polymer thus resulting in a porous structure on the microcell walls. Without the use of organic solvents, Sorrentino et al [ 20 ] and Guo et al [ 21 , 22 , 23 ] developed foams with a similar structure. They investigated the foaming of high performance polymers including PESU and found that PESU exhibited nanocellular foams whereas the other investigated polymers exhibited pores with a diameter only in the micrometer range.…”
Section: Introductionmentioning
confidence: 99%
“…A high saturation pressure (30 MPa) was also required in their work. As a rule, the production of nanocellular polymers using pure polymers demands extreme processing conditions, such as high pressures or low temperatures (under 0°C) [14,15,17,21]. Both approaches are difficult to scale-up to the industrial production, due to the technical requirements and costs associated to work at these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the diverse techniques employed for this purpose [1,12,13], foaming methods allow producing large samples without the use of organic solvents. In particular, CO 2 gas dissolution foaming has been proved to be suitable for the production of bulk nanocellular polymers using different matrices, such as poly(methyl methacrylate) (PMMA) [7,[14][15][16], polycarbonate (PC) [17], polysulfone (PSU) [18], polyphenylsulfone [19,20], or polyetherimide [21][22][23].…”
Section: Introductionmentioning
confidence: 99%